Climate change analysis of Lake Victoria outflows (Africa) using Soil and Aater Assessment Tool (SWAT) and General Circulation Models (GCMs) - Velasco, Perlie P.; Bauwens, Willy (2013)
The Soil and Water Assessment Tool (SWAT) program is used to build a hydrologic model of Lake Victoria in Africa. The impact of the climate change is then evaluated by changing the monthly rainfall and temperature in the SWAT, using four General Circulation Models (GCMs) acquired from the Intergovernmental Panel on Climate Change (IPCC) data center. The baseline period used is 19754982 and projections are made for two future periods: 2052-2059 and 2087-2094. From the results, each GCM gives different climatic projections, due to the uncertainties inherent in each GCM. Only one GCM projected a decrease in the lake outflow of about 6% (68 m(3)/s), while the other GCMs projected increases of up to 59% (720 m(3)/s). As such, the result should only serve as an estimate of the possible impact of climate changes on the outflows of the lake in view of future water resources management.
Keywords: Climate change; Soil and Water Assessment Tool (SWAT